Pemberdayaan Kelompok Perikanan Mina Usaha Bahagia Melalui Inovasi Alat Pakan dan Pelatihan Manajemen Bisnis - Yudhi Agussationo; Mazwan Mazwan; Bella Suryani; Satrio Darma Utama (Universitas Muhammadiyah Malang, 2026)
Purpose – This community empowerment program aims to enhance the independence and productivity of the Mina Usaha Bahagia Fishery Group through the implementation of an appropriate technology innovation—a fish pellet extruder machine—combined with integrated business management training. Design/methodology/approach – The program employed a needs assessment, the design and installation of a pellet extruder machine, and a series of technical and managerial training activities. Evaluation was conducted by measuring changes in production capacity, cost efficiency, and sales performance before and after the intervention. Findings – The implementation of the pellet machine significantly improved production efficiency by reducing the time required to produce 10 kg of feed from 120 minutes to 35 minutes and lowering production costs to Rp 6,500 per kilogram. Production capacity increased threefold, with enhanced pellet uniformity. On the managerial side, members demonstrated improved competencies in financial management and digital marketing, contributing to a 52% increase in group income. The establishment of a visual business identity further strengthened the group’s branding and marketing effectiveness. Originality/value – This program provides a distinctive integration of managerial training and appropriate technology application, which collectively demonstrated substantial improvements in both technical and business aspects within a community-scale fishery enterprise.